Immortalization and malignant transformation of eucaryotic cells - Stepanenko, O.A.; Kavsan, V.M. (Цитология и генетика, 2012)
This review is aimed at understanding the mechanisms of cell immortalization by different «immortalizing agents», oncogene-induced cell transformation of immortalized cells and moderate response of the advanced tumors to anticancer therapy in the light of tumor «oncogene and chromosome addiction», intra-/intertumor heterogeneity, and chromosome instability.